The Public Service Mall: Integration Quality In Education Services - Oktaviani, Safitri; Pratiwi, Ayunda; Wulandari, Sri; Erawati, Dedet (ann4publisher@gmail.com, 2025)
Background. The Public Service Mall (MPP) faces challenges, such as complex digital platforms and long service times, especially for people who are less tech-savvy. Aims. This study aims to analyze the implementation of public services at the Majalengka District Education Office through the Public Service Mall (MPP), using Indra Bastian's public service theory, which focuses on six key indicators: accountability, transparency, efficiency, effectiveness, responsiveness, and public satisfaction. Methods. This qualitative study employs interviews, observations, and documentation to collect data from various informants, including staff from the education office, school operators, teachers, and parents. Result. The results show that the Education Office has made various efforts to improve service quality through digitalization and the integration of information systems, which have positively impacted the efficiency and transparency of licensing and school administration processes. Conclusion. However, the study also identified challenges such as bureaucratic complexity in certain aspects of licensing and disparities in the equitable distribution of educational resources. Implementation. Overall, the implementation of the MPP at the Education Department of Majalengka Regency has demonstrated progress in improving public services; however, ongoing improvements are still necessary to address existing barriers and ensure more inclusive and equitable services.